1995
DOI: 10.3109/08941939509023140
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antiadhesion Barrier Does Not Prevent Anastomotic Healing in a Rabbit Model

Abstract: Intraperitoneal adhesions following surgical procedures cause considerable morbidity. Hyaluronic acid/carboxymethylcellulose (HA/CMC) films have been shown to be effective agents in decreasing adhesion formation. However, when there is an inadvertent leak of bowel contents into the peritoneum due to incomplete anastomosis, adhesion formation about a defect in order to prevent further leakage and to promote healing of the wound is important for the prevention of morbidity and mortality. The purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
0
35
0
2
Order By: Relevance
“…Medina et al [31] studied anastomotic leakage in rabbits with insufficient anastomoses. Constructing sigmoid colon anastomoses with continuous nonabsorbable sutures, a control group (n = 16) and an intervention group (n = 16) were compared.…”
Section: Animalsmentioning
confidence: 99%
“…Medina et al [31] studied anastomotic leakage in rabbits with insufficient anastomoses. Constructing sigmoid colon anastomoses with continuous nonabsorbable sutures, a control group (n = 16) and an intervention group (n = 16) were compared.…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, when HA-CMC was applied in areas with infection, it had no positive effect; possibly due to triggering foreign body reaction resulting in increased inflammation. 3,17,20 Emre et al 21 compared honey with HA-CMC in rat cecal abrasion experimental model and surprisingly showed similar effectivity. In another comparison study, Detchev et al 22 showed no superiority of hyaluronate gel on prevention of adhesions compared to serum physiologique.…”
Section: Discussionmentioning
confidence: 99%
“…In some experimental studies, wrapping Seprafilm around the anastomosis was suggested not to affect anastomotic healing adversely [35,36] . In contrast, wrapping the suture or stapler line in fresh bowel anastomoses with Seprafilm was not recommended because of the increased risk of anastomotic leakage [2,11] .…”
Section: Discussionmentioning
confidence: 99%